#TITLE_ALTERNATIVE# - DWI YOGA SUTANTO (NIM. 25511304), MAULUDIN
Modes of containers transportation needs goods increasingly making demands the availability of their supporting facilities, one of them the container port facilities as a means to carry out loading and unloading of goods. To build a container port, good design is necessary in order to optimally serve all activities that occur, and can meet the criteria of the applicable standards. This research was conducted as one of the design port reference steps, starting from data collection to stage design detail. Port design starting the supporting data collection as the basis of design in the form of historical environmental data wind speed events, current velocity, tidal water level data, topography and bathymetry maps, and soil data in the study area. Environmental modeling using the program Simulating Surface Waves (SMS) is done to get closer to the actual conditions in the study area. The Output of this modeling results used as the basis for the design criteria and the basis for determining the layout of the port. Shape, dimensions and types of ports adapted to the conditions in the study area. The next stage in port design is the calculation of the forces acting on the structure of the pier and trestle. In this study, determined the calculation of the forces acting on the structure follows the reference of Japan Code (OCDI) and regulations applicable in indonesian state. Having obtained the forces, the structural modeling using SAP2000 program. In this study modeled a jetty and trestle structure using reinforced concrete on top and steel pipe structure as a foundation. Structure modeling was conducted to determine the reliability of a building that can be seen from the Unity Check Ratio (UCR) pipe, deformation, and the style in which work on structural components. Structure modeled in SAP2000 optimized to get the value of Unity Check Ratio (UCR) is close to 1 and the value of deformation meet applicable standards. Having obtained a structure with the value of Unity Check Ratio (UCR) and deformation meet applicable standards, conducted detailing the concrete structure and the soil friction and bearing capacity calculation is based on the type of soil drilling results. Detailing concrete structures such as the determination of the number and spacing of reinforcement are used based on force output SAP2000. While the calculation of friction and bearing capacity compared to the force exerted on the pole structure SAP2000 output.